Market Orientation and Kaizen Readiness in the Automobile Dealership Context - Ryusuke KOSUGE (Annals of Business Administrative Science, 2017)
Based on the findings of Kosuge and Takahashi (2016) and existing literature, this paper hypothesized that market orientation leads to continuous improvement and tested this hypothesis using a measure of “kaizen readiness.” The results, based on responses from all the salespersons at 54 shops of an automobile dealership company, demonstrated that market orientation certainly has a strong positive correlation with kaizen readiness. The hypothesis was supported from a 2×2 cross table where market orientation and kaizen readiness were divided into high and low groups, even though it was revealed that four highly performing shops had low market orientation but high kaizen readiness. Additional investigation revealed that these four shops were not shifting toward a market orientation because they could achieve their sales targets by following their customary method of doing business.